In Vivo Subcutaneous Thermal Video Recording by Supersensitive Infrared Nanothermometers. (14th August 2017) - Ximendes, Erving C.; Rocha, Uéslen; Sales, Tasso O.; Fernández, Núria; Sanz‐Rodríguez, Francisco; Martín, Inocencio R.; Jacinto, Carlos; Jaque, Daniel
Abstract : Some of the old and unrealizable dreams of biomedicine have become possible thanks to the appearance of novel advanced materials such as luminescent nanothermometers, nanoparticles capable of providing a contactless thermal reading through their light emission properties. Luminescent nanothermometers have already been demonstrated to be capable of in vivo subcutaneous punctual thermal reading but their real application as diagnosis tools still requires demonstrating their actual capacity for the acquisition of in vivo, time‐resolved subcutaneous thermal images. The transfer from 1D to 2D subcutaneous thermal sensing is blocked in the last years mainly due to the lack of high sensitivity luminescent nanothermometers operating in the infrared biological windows. This work demonstrates how core/shell engineering, in combination with selective rare earth doping, can be used to develop supersensitive infrared luminescent nanothermometers. Erbium, thulium, and ytterbium core–shell LaF3 nanoparticles, operating within the biological windows, provide thermal sensitivities as large as 5% °C −1 . This "record" sensitivity has allowed for the final acquisition of subcutaneous thermal videos of a living animal. Subsequent analysis of thermal videos allows for an unequivocal determination of intrinsic properties of subcutaneous tissues, opening the venue to the development of novel thermal imaging‐based diagnosis tools. Abstract : The Er‐Yb@Yb‐Tm NPs are introduced as highly sensitive nanothermometers operating in the second and third biological windows. Their superior thermal sensitivity makes possible the acquisition of in vivo subcutaneous thermal videos at the small animal level. The results here presented may lead to a new era of biomedicine founded on thermal imaging based diagnosis.